ANALISIS KUALITAS DAN USULAN PERBAIKAN PROSES PRODUKSI KERIPIK TEMPE BU NIA MENGGUNAKAN METODE SEVEN TOOLS - anita; Alhaj, Ahsani Zuhdi (jurnal ATMOSPHERE, 2024)
Micro, Small, and Medium Enterprises (MSMEs) play an essential role in the national economy, including the snack food industry, such as Bu Nia’s Tempe Chips. However, defective products are still found in the production process, particularly related to texture and color. This study aims to identify the types of defects, analyze the contributing factors, and propose improvements using the Seven Tools method. Based on six months of production data analysis (January–May 2024), the defect rate was found to be 5.95%, consisting of 5.56% texture defects and 0.59% color defects. Several improvement measures were proposed, including the development of Work Instructions (WIs) for slicer machine maintenance, standardization of frying parameters, provision of larger containers to reduce pressure on the product, and separation of packaging areas to prevent contamination. Additionally, a rotational employee schedule was implemented during the Idul Fitri holiday to maintain product availability. These improvements are estimated to reduce the defect rate by up to 60%, from 5.95% to 2.6%, thereby enhancing production efficiency and product quality.